2018
DOI: 10.5194/acp-2018-6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fine particle pH for Beijing winter haze as inferred from different thermodynamic equilibrium models

Abstract: Abstract. pH is an important property of aerosol particles but is difficult to measure directly. Several studies have estimated the pH values for fine particles in North China winter haze using thermodynamic models (i.e., E-AIM and ISORROPIA) and ambient measurements. The reported pH values differ widely, ranging from close to 0 (highly acidic) to as high as 7 (neutral).In order to understand the reason for this discrepancy, we calculated pH values using these models with different assumptions 25 with regard t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(86 citation statements)
references
References 66 publications
10
71
4
1
Order By: Relevance
“…In addition to ISORROPIA‐II, we used E‐AIM to calculate the pH and the H + activity coefficients for some samples to compare the pH estimated by different models and to evaluate the effect of the H + activity coefficient on pH. For the same samples, we found the mean pH from E‐AIM was 4.1, a little bit lower than from ISORROPIA‐II (mean pH = 4.7), and the influence of H + activity coefficients on pH was weaker than that of H + molality (log 10 γ(H + ) = 0.32 ± 0.22, γ(H + ) is the activity coefficient of H + ), which agrees well with other recent assessments (Jia et al, ; Song et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to ISORROPIA‐II, we used E‐AIM to calculate the pH and the H + activity coefficients for some samples to compare the pH estimated by different models and to evaluate the effect of the H + activity coefficient on pH. For the same samples, we found the mean pH from E‐AIM was 4.1, a little bit lower than from ISORROPIA‐II (mean pH = 4.7), and the influence of H + activity coefficients on pH was weaker than that of H + molality (log 10 γ(H + ) = 0.32 ± 0.22, γ(H + ) is the activity coefficient of H + ), which agrees well with other recent assessments (Jia et al, ; Song et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Aerosol acidity, as characterized by pH (hydrogen ion activity expressed on a logarithmic scale), influences aerosol growth and concentrations via secondary aerosol formation and gas‐aerosol partitioning (Jang et al, ; H. Y. Li et al, ; Meskhidze et al, ; Pattatyus et al, ; Surratta et al, ). Fine particulate matter, much of which can be acidic (Lawal et al, ; Silvern et al, ; Song et al, , ; Weber et al, ), is also associated with harmful effects on human health. Particulate matter can also have negative environmental effects, such as reduced visibility and damage to ecological systems and historical monuments (Bouwman et al, ; Cheng et al, ; Huo et al, ; Ren et al, ; Tang et al, ; W. Wang, Liu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements from fog/low cloud water in Beijing showed a pH of 5.2–6.2 between 1999 and 2006 (Jiang et al, ). More recent observations infer an aerosol pH of ~4–5 during haze events (Guo et al, ; Liu et al, ; Song et al, ), which implies a somewhat higher pH in cloud droplets due to ion exchange between cloud and aerosol during cloud processing (Ervens, ; Liu et al, ). In addition, precipitation in Beijing reveals pH values of ~5.5–6 (Huo et al, ; Tang et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…T was varied by ±5K (288K and 298K) and RH by ±20% (30% and 70%), respectively. Although particle‐phase change (solid crystals may precipitate out from liquid phase) is not considered when RH drops below 30%‐40%, Song et al have shown that the metastable (a single liquid phase) and stable (solid + liquid phases) solutions predict similar pH.…”
Section: Methodsologymentioning
confidence: 99%